Application of a free preputial tube graft coupled with urethral plate urethroplasty combined with a Buck's fascia integral covering for the single-stage repair of severe hypospadias - Zhou, Wei; Li, Changpei; Xia, Fan; Zhang, Qi; Chen, Yanxing (Frontiers in Surgery, 2023)
Objective To assess the outcome of a free preputial tube graft coupled with urethral plate urethroplasty combined with a Buck's fascia integral covering (BFIC) for the single-stage repair of severe hypospadias in children. Materials and methods A retrospective study was performed on 40 children with hypospadias who were treated in our hospital from December 2017 to February 2022. The inclusion criteria were as follows: (1) the patient had proximal hypospadias, or penile curvature over 30° after degloving the penis; and (2) the patient underwent surgery for hypospadias for the first time. A free preputial tube graft coupled with urethral plate urethroplasty combined with a Buck's fascia integral covering was performed, and all patients were followed up for more than 6 months. Results After degloving the foreskin, the urethral orifice was retracted to the perineum and scrotum in 20 cases, penoscrotal in 8 cases, and penile in 12 cases. Single-stage repair was achieved without complications in 34 (85%) patients. The remaining six patients experienced postoperative complications: urethrocutaneous fistula occurred in five cases and glans dehiscence with urethrocutaneous fistula in one case. No urethral diverticulum occurred in any case. A neomeatus with a vertically oriented slit-like appearance was achieved at the tip of the glans in all cases, with one exception. Conclusion The single-stage operation with a free preputial tube graft coupled with urethral plate urethroplasty combined with a Buck's fascia integral covering in the treatment of severe hypospadias achieves favorable functional and cosmetic outcomes.